The global economic crisis and FDI flows to emerging markets: for the first time ever, emerging markets are this year set to attract more than half of global FDI flows - Laza Kekic (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2009)
For the first time ever, emerging markets are set to attract more FDI inflows than developed countries in 2009. This Perspective examines this prospect, based on an analysis of the severe downturn of investment flows worldwide this year.
Keywords: 330